Um olhar para as relações na introdução da educação inclusiva no colégio militar de Porto Alegre : reflexões a partir de Buber - Becker, Caroline (2019)
The theme Special Education, from the perspective of Inclusive education, permeates several academic researches, in the national and international sphere, especially after the Warnock Report. However, in the context of Military Education these discussions started to be constituted only now. Thus, this volume presents the Doctoral thesis in Education which addresses the perceptions of professionals involved in the process of introduction to inclusive education in the Military School of Porto Alegre (CMPA), considering the educational and military premises of the Military School system of Brazil. Therefore, it investigates the introduction to inclusive education in the Military School of Porto Alegre and presents the reflection on the question: what is the perception of professionals and teachers about the implementation process of Inclusive Education at the Military School of Porto Alegre? As a general objective it aims to understand the perception of professionals and teachers who work in the Military School of Porto Alegre regarding the introduction of Inclusive Education in the Institution. While specific objectives are to analyze the changes resulting from the beginning of Inclusive Education in the Military School of Porto Alegre, in the action of teacher and professionals involved in the educational process, to understand the process to the introduction of the Inclusive Education in the Military College of Porto Alegre and to develop guidelines based on the results obtained in the research, so that itsupports the systematization of the Inclusive Education in the Military School of Porto Alegre. This proposal is based on a qualitative approach with emphasis in the research-action (Thiollent, 2009). As a theoretical reference the main author is the philosopher Martin Buber. As result, it presents the importance of relations, proposed by Buber, for the collective pursuit for solutions that promote the physical, social and institutional accessibility of inclusive education in a traditional school.